Mechanical vs manual cleaning of hospital beds: a prospective intervention study. Issue 2 (June 2015) - Hopman, J.; Nillesen, M.; de Both, E.; Witte, J.; Teerenstra, S.; Hulscher, M.; Voss, A.
Summary: Background: Cleaning regimens for hospital beds were evaluated in the context of a rising prevalence of highly resistant micro-organisms and increasing financial pressure on healthcare systems. Dutch hospitals have to choose between standardized, mechanical bed-washers advised in national guidance and manual cleaning. Aim: To evaluate the quality of mechanical and manual bed-cleaning regimens. Methods: The multi-faceted analysis of bed-cleaning regimens consisted of three steps. In Step 1, the training of the domestic service team was evaluated. In Step 2, the cleaning quality of manual and mechanical regimens was assessed. Soiled beds, obtained at random, from different departments were evaluated using microbiological analysis ( N = 40) and ATP ( N = 20). ATP and microbiological contamination were measured in five predetermined locations on all beds. In Step 3, manual cleaning was introduced over a two-month pilot study at the surgical short-stay unit, and beds from other departments were processed according to the 'gold standard' mechanical cleaning. ATP levels were evaluated in three locations on 300 beds after cleaning. Findings: Training was found to improve the quality of cleaning significantly. Mechanical cleaning resulted in significantly lower ATP levels than manual cleaning. Conclusions: Mechanical cleaning shows less variation and results in consistently lower ATP levels than manual cleaning.